Students’ performance in clinical class II composite restorations: a case study using analytic rubrics - Arwa Daghrery; Ghadeer Saleh Alwadai; Nada Ahmad Alamoudi; Saleh Ali Alqahtani; Faisal Hasan Alshehri; Mohammed Hussain Al Wadei; Naif Nabel Abogazalah; Gabriel Kalil Rocha Pereira; Mohammed M Al Moaleem (BMC Medical Education)
Abstract Background The analytical rubric serves as a permanent reference for guidelines on clinical performance for undergraduate dental students. This study aims to assess the rubric system used to evaluate clinical class II composite restorations performed by undergraduate dental students and to explore the impact of gender on overall student performance across two academic years. Additionally, we investigated the relationship between cumulative grade point averages (CGPAs) and students’ clinical performance. Methods An analytical rubric for the assessment of clinical class II composite restoration in the academic years of 2022/2023 and 2023/2024 was used by two evaluators. These two evaluators were trained to use the rubric before doing the evaluations. The scores were based on a 4-point scale for the evaluation of five major parameters for pre-operative procedures (10 points), cavity preparation (20 points), restoration procedures (20 points), and time management (4 points). At the same time, chairside oral exam parameter was 15 points based on a 5-point scale. Descriptive statistics were calculated for the different analytical rubric parameters, and the independent t-test was used to compare the scores between the student groups and the evaluators. Other tests, such as the Kappa test and Pearson’s correlation coefficient, were used to measure the association among CGPA, evaluators, and gender participants. Results The overall score out of 69 slightly increased for females/males (61.28/59.42) and (61.18/59.49) in the 2022/2023 and 2023/2024 academic years, respectively, but the differences were not statistically significant. In the 2022/2023 academic year, female students scored significantly higher than male students in pre-operative procedures, as evaluated by both evaluators (p = 0.001), and in time management, as assessed by both evaluators (p = 0.031). The Kappa test demonstrated a moderate to substantial level of agreement between the two evaluators in both academic years. Strong and significant correlations were noted between students’ CGPA and some tested parameters (p = 0.000). Conclusion The overall performance was very good and high among both genders, but it was marginally higher among females than among males. This study found some differences in performance between male and female students and variability in the evaluations by the two raters ranging from moderate to substantial agreement and similar performances for students with different CGPA.